2014
DOI: 10.4028/www.scientific.net/amm.651-653.1056
|View full text |Cite
|
Sign up to set email alerts
|

Research of Li-Ion Battery’s Equalizer Circuit Based on TL431

Abstract: Li-ion battery, as a new type of energy storage equipment, has small size, large power density, high individual voltage, low rate of self-discharging and small self-resistance etc. It substitutes the traditional power battery in AGV.In practical process, due to the difference of battery cells, after a period of charge-discharge time, the upper and lower voltage limits of every unit of batteries become various, seriously affecting the system performance. The idea of upper and lower equalizer is released for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The energy transfer unit of the active equalization method may be based on the inductor, [7][8][9] the transformer, 10-12 the combination of inductor and capacitor (LC resonant circuit [13][14][15] and dc-dc converter [16][17][18][19] ), or the capacitor. [20][21][22][23][24][25] Note that voltage difference is small between cells and is large between cell and pack. So, the energy transfer unit commonly uses inductor, capacitor, or their combination for C2C topology and uses transformer for C2P, P2C, or C2P2C topology.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The energy transfer unit of the active equalization method may be based on the inductor, [7][8][9] the transformer, 10-12 the combination of inductor and capacitor (LC resonant circuit [13][14][15] and dc-dc converter [16][17][18][19] ), or the capacitor. [20][21][22][23][24][25] Note that voltage difference is small between cells and is large between cell and pack. So, the energy transfer unit commonly uses inductor, capacitor, or their combination for C2C topology and uses transformer for C2P, P2C, or C2P2C topology.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional capacitor-based equalizers use the switched capacitor (SC) method 20,21 or the flying capacitor (FC) method. 22 The original SC method can only exchange energy between two adjacent cells. Several improvements have been made for this method, such as the starstructured SC, mesh-structured SC, and delta-structured SC [23][24][25] for the purpose of providing flexible energy exchange paths.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if apply the power designed above in AGV system, after a period of time of discharge and charge with large current, it is found that the upper limit voltage of every cell is seriously differen.The reason is that the difference between every cell has been ignored in the initial design of li-ion battery protection. In this case, referring to the foreign design released, li-ion upper equalizer circuits are designed [4][5].…”
Section: Introductionmentioning
confidence: 99%